Mindful approach to University education - Broggi F; Bomba M; Rimondini M; Mutti M; Pasta S; Ricci C; Tagliabue L; Valsecchi S; Monaco E; Neri F; Oggiano S; Nacinovich R (Advances in Medical Education and Practice, 2016)
Fiorenza Broggi,1 Monica Bomba,1 Michela Rimondini,2 Maura Mutti,1 Sara Pasta,1 Chiara Ricci,1 Luca Tagliabue,1 Silvia Valsecchi,1 Elide Monaco,1 Francesca Neri,1 Silvia Oggiano,2 Renata Nacinovich,1 1Department of Child and Adolescent Psychiatry, San Gerardo Hospital, University of Milano–Bicocca, Monza, 2Department of Clinical Psychology, University of Verona, Italy Abstract: A mindful approach to education and training could improve students’ reflective capacities and have positive effects on clinical practice because it facilitates a helping relationship. The main aims of this study were to investigate whether participation in a mindful-based University training was associated with increases in mindfulness skills as measured by the 5-Facet M Questionnaire, and to present the Italian validation of the questionnaire. Sixty-seven students from the course Neuro and Psychomotor Therapy were enrolled. They filled in the self-administered 5-Facet M Questionnaire before and 1 month after a mindfulness-based training, focused on role-playing and followed by a feedback group discussion. The Italian version of the 5-Facet M Questionnaire had good psychometric properties. The pre- and post-training analysis showed a significant increase in the subscale ‘Observing’. Findings suggest that role-playing and feedback group sessions are valid tools to improve students’ mindfulness skills. Keywords: mindfulness, role play, self-awareness, communication skills, insight, reflective capacities, feedback